2017
DOI: 10.5005/jp-journals-10033-1294
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three-port vs Four-port Laparoscopic Cholecystectomy in a Medical College in the Periphery

Abstract: Aims and objectives:To compare three-port laparoscopic cholecystectomy (LC) with four-port LC in chronic calculous cholecystitis patients. We compared the feasibility of the procedure, total operative time, postoperative pain, incidence of complications, and cosmetic results. Materials and methods:The present study was conducted in the Department of Surgery at Maharishi Markandeshwar Institute of Medical Sciences and Research, Mullana, Ambala. Totally, 200 adult patients of cholelithiasis with chronic cholecys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…Six RCTs and 2 systematic reviews compared 2- and 3-port LC against 4-port LC [ [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ] ( Table 2 ). Two-incision approach differed slightly between studies: Poon et al used a modified operating telescope through 1 of the ports [ 16 ], Tavassoli et al used two 5-mm ports inserted into the umbilical incision and one 10-mm port in the hypogastrium [ 17 ], and Sreenivas et al used 2 ports and 2 additional needlescopic transabdominal graspers [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six RCTs and 2 systematic reviews compared 2- and 3-port LC against 4-port LC [ [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ] ( Table 2 ). Two-incision approach differed slightly between studies: Poon et al used a modified operating telescope through 1 of the ports [ 16 ], Tavassoli et al used two 5-mm ports inserted into the umbilical incision and one 10-mm port in the hypogastrium [ 17 ], and Sreenivas et al used 2 ports and 2 additional needlescopic transabdominal graspers [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…All 4 studies comparing 3-LC and 4-LC demonstrated less postoperative pain and quicker return to work/physiologic baseline among 3-LC patients [ [12] , [13] , [14] , [15] ]. For 2-LC versus 4-LC, Tavassoli and Sreenivas found decreased pain and quicker return to baseline after 2-LC [ 17 , 18 ], whereas Poon did not find improvements in pain [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of minimal access surgery for gallbladder surgery has revolutionized the treatment of gallstones [1]. Laparoscopic cholecystectomy (LC) has become the gold standard treatment for symptomatic uncomplicated cholelithiasis and replaced the open cholecystectomy (OC).…”
Section: Introductionmentioning
confidence: 99%